The Impact of Free Fire Game Addiction on the Learning Aggressiveness of Middle School Students from Albert Bandura's Perspective - Helmi yahya; Anas Ahmadi (International Journal of Economics, Science, and Education, 2024)
Purpose: The aim of this research is to determine the impact felt by students because they are addicted to playing the online game Free Fire. The research is expected to be able to determine the influence of the habit of playing online games on students' learning aggressiveness at junior high school (SMP) level with the perspective of Albert Bandura's social emotional psychology Design/methodology/approach: The research was conducted involving 20 junior high school students who had been determined by the researcher using the qualitative descriptive case study method. Findings: The results of the research show that students felt different impacts, students felt aggressive and enthusiastic about learning after completing the online game Free Fire which had been determined by the time by the students, but there were also those who were not enthusiastic about learning. Research limitations/implications: Students' aggressiveness is one of the important points for achieving fast and enjoyable learning goals. Practical implications: The research will have an impact on the condition of students while in class and will be able to reveal the impact caused by the habit of playing free fire online agility games which can be good for students' enthusiasm for learning Originality/value: This research has never been carried out by anyone else, the data used was taken directly in the field and directly observed students' learning activities.